2020
DOI: 10.3390/pr8060721
|View full text |Cite
|
Sign up to set email alerts
|

Phenol Degradation Kinetics by Free and Immobilized Pseudomonas putida BCRC 14365 in Batch and Continuous-Flow Bioreactors

Abstract: Phenol degradation by Pseudomonas putida BCRC 14365 was investigated at 30 °C and a pH of 5.0–9.0 in the batch tests. Experimental results for both free and immobilized cells demonstrated that a maximum phenol degradation rate occurred at an initial pH of 7. The peak value of phenol degradation rates by the free and immobilized cells were 2.84 and 2.64 mg/L-h, respectively. Considering the culture at 20 °C, there was a lag period of approximately 44 h prior to the start of the phenol degradation for both free … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 48 publications
1
5
0
Order By: Relevance
“…Lower growth at 300 mg/L phenol could be explained by the growth-limiting factor of the substrate (carbon source) concentration, while the lower growth at phenol concentration above 1000 mg/L suggest the toxic effect of phenol on Sphe3 cells. A similar phenomenon of increasing growth and degradation efficiency with increasing the substrate concentration and then decreasing above a concentration threshold, indicating substrate inhibition kinetics has been reported by others [ 2 , 44 , 45 ].…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…Lower growth at 300 mg/L phenol could be explained by the growth-limiting factor of the substrate (carbon source) concentration, while the lower growth at phenol concentration above 1000 mg/L suggest the toxic effect of phenol on Sphe3 cells. A similar phenomenon of increasing growth and degradation efficiency with increasing the substrate concentration and then decreasing above a concentration threshold, indicating substrate inhibition kinetics has been reported by others [ 2 , 44 , 45 ].…”
Section: Resultssupporting
confidence: 86%
“…Immobilized Bacillus sp. SAS19 exhibited lower degradation activity compared to free bacterial cells [ 52 ], while immobilized Pseudomonas putida BCRC 14365 showed a slightly lower degradation rate of phenol than the free cells [ 44 ]. Moreover, immobilized Acinetobacter sp.…”
Section: Resultsmentioning
confidence: 99%
“…Our findings are in agreement with Yordanova et al [33], who found that the degradation of phenol and 2,4-DCP by immobilized cultures was faster than 2-CP and 4-CP degradation. In addition, numerous reports demonstrated that the immobilized cultures process the highest removal potency for different CPs than free cultures [34][35][36].…”
Section: Discussionmentioning
confidence: 99%
“…The results of the present investigation also showed that the immobilized cultures and enzymes were relatively stable for a long time. The reused immobilized cultures and enzymes can be considered a crucial parameter in an industrial treatment, which determines the effectiveness of biotransformation over time [36]. Luffa pulp (as an adsorbed solid support) recorded lower cell leakage, maximum mechanical stability, and resistance to biological and chemical degradation, making it suitable for an extended period of repetition [43].…”
Section: Discussionmentioning
confidence: 99%
“…Because of the advantages of complete degradation and no secondary pollution, biodegradation is widely regarded as a practical, economical and promising method (Azadi & Shojaei 2020;Lee et al 2020;Nogina et al 2020). Various kinds of microorganisms with the ability of degradation of phenol have been favored, such as Pseudomonas, Acinetobacter, Yeasts, and activated sludge with a wide variety of microorganisms (Filipowicz et al 2020;Lin & Cheng 2020;Liu et al 2020;He et al 2021). In general, as the increase of the concentration for hazardous pollutants, the ability of natural microorganisms for degradation is decreased.…”
Section: Introductionmentioning
confidence: 99%